An economic model of the drives from Friston’s free energy perspective - Sikora, Gustaw (Frontiers in Human Neuroscience, 2022)
This paper is focused on the theory of drives, particularly on its economic model, which was an integral part of Freud’s original formulation. Freud was aiming to make a link between the psychic energy of drives and the biophysical rules of nature. The further development of psychoanalytic theory, in various attempts to comprehend the theory of drives, can be described as taking different approaches. Some of them equate drives with bodily impulses, others abandon the economic model, a few stay with Freud’s original model. I believe that the Friston notion of free energy and the hierarchical model of the brain allows us to develop this model and to integrate the economic model into some contemporary theories of drives. I argue against those theories equating drives with biological impulses. My arguments are supported by Freud’s project itself but also by recent developments within neuro-psychoanalysis describing the process of mentalizing homeostasis, interoceptive signals and relations with caregivers. I argue for those theories which see the drives as psychic forces, which through developmental processes and cathexes acquire aims and objects, and become intertwined with impulses originating internally and externally, such as affect, interoceptive impulses, perception of the external world, and impulses from erotogenic zones in particular. Here, I present my analysis of the compatibility and consistency of free energy and the hierarchical model perspective, and two psychoanalytical traditions of thoughts: French psychoanalysis and the post-Kleinian school of British psychoanalysis. In particular, my analysis focuses on the contemporary Kleinian notion of unconscious phantasies, especially Bronstein’s description of their semiotic aspects. Secondly, I look at Segal’s view of drives as dialectic forces of adaptation versus conservatism. Analysing the French tradition, I focus on Green’s perspective on the drives, Lacan’s distinction between drives and desire, and Penot’s description of the process of subjectivation. I conclude that free energy, as described by Friston, can be seen as a source of the drives’ energy and the process of minimising it is an equivalent of what Freud described as binding the free energy, in which psychic unbound energy acquires distinctive features and becomes bound.